2005
DOI: 10.1111/j.1442-200x.2005.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐arginine and L‐carnitine in hypoxia/reoxygenation‐induced intestinal injury

Abstract: Oxidative stress contributes to the pathogenesis of H/R-induced intestinal injury. The glutathione redox cycle may have a crucial role in the H/R-induced intestinal injury. L-arginine and L-carnitine supplementations ameliorate the histological evidence of H/R-induced intestinal injury and decrease lipid peroxidation but do not alter the glutathione-related antioxidant enzyme activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Although the etiology of NEC remains uncertain, hypoxia and ischemia appear to play an important role in the pathogenesis of this ischemic bowel disease [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the etiology of NEC remains uncertain, hypoxia and ischemia appear to play an important role in the pathogenesis of this ischemic bowel disease [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 98%
“…This protocol was not performed on the control group. At the sixth hour after H/R, all rat pups in all groups were killed on the fourth day of life [7]. Histopathologic injury score (HIS) and MDA, NO, GSH (total thiol), and GSH-Px activities were measured on intestinal tissue samples.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue MDA content, the last product of lipid breakdown caused by oxidative stress, is considered to be a good indicator of radical-induced lipid peroxidation [44] . In this study, we found increased intestinal MDA levels in the burnt mice groups, suggesting that in our experimental conditions, after 24 h from manipulation, a significant increase of oxidative stress occurs.…”
Section: Discussionmentioning
confidence: 99%